FAKTOR-FAKTOR YANG MEMPENGARUHI KURANGNYA MINAT BELAJAR MATEMATIKA SISWA KELAS VI SD NEGERI 10 KOTA BARU - Wahyunda, Rahmi; Wibowo, Deki; Lestari, Novika (JURNAL PENDIDIKAN DAN PEMBELAJARAN SEKOLAH DASAR, 2023)
The purpose of this studi was to determine the factors affecting the lack of interest in lerning mathematics for sixth grade students of SD Negeri 10 Kota Baru. The subjects in this study were students and teacher of mathematics six grade SDÂ  Negeri 10 Kota Baru.This study uses qualitative research methods,Â  data collection techniques in this study using interviews and documentation, research instruments using interview sheets. Data analysis in this study is data collection, data reduction, data presentation and conclusion drawing. While the validity of the data used is triangulation data sources.The results of the study found that the factors that influence the lack of interest in learning mathematics for grade VI students of SD Negeri 10 Kota Baru are factors from within students (internal) and factors from outside (external). The internal factors include student attitudes, student motivation and intelligence, while external factors include the family environment, social environment, as well as teachers and how to educate. The attitude of students who are not good, and low motivation towards a learning and the level of student ability that is less can result in a lack of student interest in a learning. In addition, the way teachers teach is less effective, the family environment and social environment are not good also affect students' interest in learning mathematics.